2012
DOI: 10.3354/ame01576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ocean acidification on cyanobacteria in the subtropical North Atlantic

Abstract: OPEN PEN ACCESS CCESSAt sea ocean acidification experiments show contrasting responses between dominant unicellular and colonial natural cyanobacteria populations. Insets (top to bottom): Synechococcus (epifluorescence microscopy), Prochlorococcus (brightfield microscopy) and Trichodesmium (bright-field microscopy) Photos: S. Jaeger and M. Lomas

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 50 publications
3
54
2
Order By: Relevance
“…In this situation, an increase in CO 2 and bicarbonate concentration can result in a substantial energetic savings for the cells. Such savings probably explain the beneficial effects of high pCO 2 on N 2 and C fixation observed in P-and Fe-replete incubations of Trichodesmium thiebautii colonies collected from the field (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation, an increase in CO 2 and bicarbonate concentration can result in a substantial energetic savings for the cells. Such savings probably explain the beneficial effects of high pCO 2 on N 2 and C fixation observed in P-and Fe-replete incubations of Trichodesmium thiebautii colonies collected from the field (19).…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation of N 2 fixation and growth at elevated pCO 2 has been observed in both laboratory and field studies (11)(12)(13)(14)(15)(16)(17)(18)(19). The beneficial effect of high pCO 2 has been attributed largely to the down-regulation of the CCM, which saves energetic resources for other cellular processes, such as N 2 fixation (14, 15).…”
mentioning
confidence: 99%
“…Moreover, cell lines kept in culture may not even have retained the physiological characteristics of the original clones (Joint et al, 2011). Natural community perturbation experiments have the potential to provide a greater environmental relevance through investigation of the entire (microbial) ecosystem structure and function in an environment better approximating natural conditions (Tortell et al, 2002;Delille et al, 2005;Engel et al, 2005;Hare et al, 2007;Feng et al, 2009;Hopkinson et al, 2010;Lomas et al, 2012;Losh et al, 2012). However, interpreting the results of such field experiments can be complicated by the multiple biogeochemical feedbacks and food web interactions, which characterise responses to perturbation in any complex natural community Krause et al, 2012;Brussaard et al, 2013).…”
Section: S Richier Et Al: Phytoplankton Responses and Associated Camentioning
confidence: 99%
“…The main consequences of this increase which will affect planktonic organisms are (a) seawater acidification, (b) increase of seawater temperature, (c) water column stratification, (d) expansion of OMZs, and (e) desertification of terrestrial systems and associated increase of desert dust inputs to the ocean (Boyd and Doney, 2002;Jickells, 2005;Stramma et al, 2008b). While seawater acidification can either enhance photosynthetic activity in some species, or be harmful for others (Malakoff, 2012), seawater warming and stratification will likely enhance the proliferation of diazotrophic cyanobacteria such as Trichodesmium (Lomas et al, 2012), although their response to increased pCO 2 levels may depend on a variety of environmental factors . Indeed, culture experiments have revealed that the length of Trichodesmium filaments and their N 2 fixation rates increase when exposed to increasing levels of CO 2 (Levitan et al, 2007).…”
Section: What Is There Left To Be Known?mentioning
confidence: 99%